MENUMBUHKAN GIRAH KEISLAMAN DAN MINAT AKADEMIK SANTRI (STUDI TENTANG CORAK LITERATUR KEAGAMAAN DI PONDOK PESANTREN AL-MUKMIN NGRUKI SOLO JAWA TENGAH) - HURIYUDIN HURIYUDIN (Al Qalam, 2019)
This article tries to identify kinds, study areas and discourses contained in religious literatures of Pondok Pesantren AI-Mukmin, Ngruki, Sukoharjo, Solo. Moreover, it also tries to classify the texts, to analyze the content, as well as to study its relevance with socio-religious problems in Indonesia. Data are collected through interoiews, direct obseroation, document analysis, and content analysis to religious books it uses. Based on the data analysis, it is clear to demonstrate that in its Islamic theology, this pesantren generally promotes literal-scriptural-based religious thought issued by Muhammad ibn 'Abd al-Wahhtib. As a consequence of having this theological characteristics, Pesantren AI-Mukmin doesn't give a sufficient appreciation to classical-religious treasures of yellow books written by traditional ulama such as al-Gazali as y-Syafi'i, Abu Hanifah, Abu Hasan al-Asry’i; the thoughts of Muslim philosophers, as well as ulama and other Muslim-rational thinkers. Another implication of this theological characteristics is that AI-Mukmin is built by spirit of cadre forming in order to erect the goal of Muslim civilization in the form of imamah and khilafah Islamiyah as an institution that must absolutefy exist for implementing Islamic Shari'a. Key Words: Pesantren AI-Mukmin, Literature, Text, Religious Thoughts